2019
DOI: 10.20546/ijcmas.2019.811.186
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies for Yield and Fibre Quality Related Traits in Upland Cotton (Gossypium hirsutum L.) and Identification of Superior Transgressive Segregants

Abstract: Improvement of agronomic traits and fibre quality in cotton requires detailed information on genetic variation available in the population. The objective of this study was to investigate variability, heritability and character association in nine agronomic and five fibre quality traits among 220 recombinant inbred lines (RILs) derived from MCU 5 and TCH1218. The study was undertaken during kharif 2018-19 at Department of cotton, TNAU, Coimbatore. High PCV and GCV were exhibited by number of monopodia per plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Erande et al (2014) and Monisha et al (2018) reported a significantly positive association of GOT with yield, the number of bolls and seeds per boll. The results of path analysis were in accordance with Nandhini et al (2019) and Kumbhar et al (2020), who suggested direct positive effects of boll weight on yield. Manonmani et al (2019) and Ali et al (2020) reported a direct positive effect of seed per boll on yield.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Erande et al (2014) and Monisha et al (2018) reported a significantly positive association of GOT with yield, the number of bolls and seeds per boll. The results of path analysis were in accordance with Nandhini et al (2019) and Kumbhar et al (2020), who suggested direct positive effects of boll weight on yield. Manonmani et al (2019) and Ali et al (2020) reported a direct positive effect of seed per boll on yield.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been reported by Reddy et al (2019) while Kumbhar et al (2020) reported a significantly positive association of plant height with sympodial branches. Erande et al (2014) and Nandhini et al (2019) reported a non-significant and positive correlation of the number of monopodial branches with GOT. Salahuddin et al (2010) found that at the phenotypic level, yield was positively associated with sympodial and bolls.…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that heritability is due to additive gene action and hence direct selection will be profitable in these traits. Previous studies bySahar et al (2021),Abro et al (2021),Nandhini et al (2019), Nikhil et al (2018 andShao et al (2016) documented similar results. Higher heritability with medium genetic advance was found for days to 50 per cent flowering (66.77 %, 10.85 %), plant height (80.90 %, 15.97 %), seed index (72.67 %, 12.53 %) and fibre strength (83.20 %, 13.36 %).…”
supporting
confidence: 68%